Moderasi Beragama dan Normalisasi Pengamalan Ajaran Agama dalam Upaya Harmonisasi Ummat Beragama dan Upaya Menangkal Kekeliruan Pemahaman Agama dan Tindakan Intoleran - Suaidi Suaidi (Jurnal Budi Pekerti Agama Islam, 2025)
Misunderstanding of religion will have an impact on the practice and acts of violence in the name of religion, such as intolerant, radical and even terrorist acts. These actions are often used as a shield for orders and in the name of religion, as if religion legitimizes violence and hostility. In truth, religion brings a message of peace, tolerance and mutual respect for differences. This study aims to provide a contribution, that every religion teaches to socialize and live peacefully and harmoniously, even though living in the midst of a society with different beliefs. In fact, religious adherents are able to create peace and avoid conflict, because the core teachings of every religion are to build harmony between humans even though they have different beliefs. Religious moderation is one of the major efforts to re-actualize religious adherents that conflict between fellow human beings is prohibited by religion.